Potential Role and Impact of Peripheral Blood Mononuclear Cells in Radiographic Axial Spondyloarthritis-Associated Endothelial Dysfunction - Patricia Ruiz-Limon; Maria L. Ladehesa-Pineda; Clementina Lopez-Medina; Chary Lopez-Pedrera; Maria C. Abalos-Aguilera; Nuria Barbarroja; Isabel Arias-Quiros; Carlos Perez-Sanchez; Ivan Arias-de la Rosa; Rafaela Ortega-Castro; Alejandro Escudero-Contreras; Eduardo Collantes-Estevez; et al. (Diagnostics, 2021)
Endothelial dysfunction (ED) is well known as a process that can lead to atherosclerosis and is frequently presented in radiographic axial spondyloarthritis (r-axSpA) patients. Here, we investigated cellular and molecular mechanisms underlying r-axSpA-related ED, and analyzed the potential effect of peripheral blood mononuclear cells (PBMCs) in promoting endothelial injury in r-axSpA. A total of 30 r-axSpA patients and 32 healthy donors (HDs) were evaluated. The endothelial function, inflammatory and atherogenic profile, and oxidative stress were quantified. In vitro studies were designed to evaluate the effect of PBMCs from r-axSpA patients on aberrant endothelial activation. Compared to HDs, our study found that, associated with ED and the plasma proatherogenic profile present in r-axSpA, PBMCs from these patients displayed a pro-oxidative, proinflammatory, and proatherogenic phenotype, with most molecular changes noticed in lymphocytes. Correlation studies revealed the relationship between this phenotype and the microvascular function. Additional in vitro studies confirmed that PBMCs from r-axSpA patients promoted endothelial injury. Altogether, this study suggests the relevance of r-axSpA itself as a strong and independent cardiovascular risk factor, contributing to a dysfunctional endothelium and atherogenic status by aberrant activation of PBMCs. Lymphocytes could be the main contributors in the development of ED and subsequent atherosclerosis in this pathology.